2011
DOI: 10.1037/a0021938
|View full text |Cite
|
Sign up to set email alerts
|

Child teacher relationship training: A phenomenological study.

Abstract: This article examines the findings from a phenomenological study of 10 early childhood and Pre-Kindergarten teachers who participated in Child Teacher Relationship Training (CTRT). Results present the essence of the participants' largely affirmative experience of CTRT in regard to general applicability and interrelatedness between the CTRT model and the teachers' views on the importance of the child-teacher relationship. Implications for early childhood education and the impact of the child-teacher relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
(56 reference statements)
3
21
0
Order By: Relevance
“…Specific to education, five studies indicated positive outcomes for both teacher and students in pre–K settings. Specifically, teachers in experimental groups increased their empathic interactions with students; improved their reports of child adaptive, internalized, and overall behaviors; improved in CTRT skills during the training; and experienced a positive impact on classrooms (Helker & Ray, 2009; Lindo et al, 2014; Morrison & Bratton, 2010; Post et al, 2004; Sepulveda et al, 2011; D. M. Smith & Landreth, 2004).…”
Section: Teachers’ Experiences In the Classroommentioning
confidence: 99%
“…Specific to education, five studies indicated positive outcomes for both teacher and students in pre–K settings. Specifically, teachers in experimental groups increased their empathic interactions with students; improved their reports of child adaptive, internalized, and overall behaviors; improved in CTRT skills during the training; and experienced a positive impact on classrooms (Helker & Ray, 2009; Lindo et al, 2014; Morrison & Bratton, 2010; Post et al, 2004; Sepulveda et al, 2011; D. M. Smith & Landreth, 2004).…”
Section: Teachers’ Experiences In the Classroommentioning
confidence: 99%
“…Collaborative programs designed to support teachers can be implemented by school-based play therapists and school counselors by creating partnerships with teachers to support students. One such program is child–teacher relationship training (CTRT; Sepulveda, Garza, & Morrison, 2011), an adaptation of child–parent relationship training (CPRT; Landreth & Bratton, 2006). Utilizing the same framework and model as CPRT, CTRT focuses on maximizing the pre-existing relationship between teachers and students through the attitudes and skills of child-centered play therapy (CCPT; Landreth, 2012).…”
mentioning
confidence: 99%
“…Research indicates that CTRT is an effective intervention for increasing teachers’ ability to demonstrate relationship-building skills (Helker & Ray, 2009; Hess, Post, & Flowers, 2005; Post, McAllister, Sheely, Hess, & Flowers, 2004; Sepulveda et al, 2011) as well as reducing students’ behavioral problems (Coggins, 2016; Helker & Ray, 2009; Morrison Bennett & Bratton, 2011; Post et al, 2004). Research also shows that CTRT has helped teachers build stronger relationships with their students, build students’ self-esteem, and contributed to the teachers’ commitment to their work and to their students (Post et al, 2020).…”
mentioning
confidence: 99%
“…Research shows that CTRT can be an effective intervention for increasing teachers' ability to demonstrate relationship-building skills (Helker & Ray, 2009;Hess et al, 2005;Post et al, 2004;Sepulveda et al, 2011) as well as reducing students' behavioral problems (Coggins, 2016;Helker & Ray, 2009;Morrison Bennett & Bratton, 2011; This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
mentioning
confidence: 99%